Ethical considerations for psychedelic-assisted therapy in military clinical settings - Hoener, Scott (Journal of medical ethics, 2024)
Psychedelic treatments, particularly 3,4-methylenedioxymethamphetamine (MDMA)-assisted and psilocybin-assisted therapies, have recently seen renewed interest in their clinical potential to treat various mental health conditions. Clinical trials for both MDMA-assisted and psilocybin-assisted therapies have shown to be highly efficacious for post-traumatic stress disorder and major depression. Recent research trials for psychedelic-assisted therapies (PAT) have demonstrated that although they are resource-intensive, their effects are rapid-acting, durable and cost-effective. These results have generated enthusiasm among researchers seeking to investigate psychedelic therapies in active-duty service members of the US military, particularly those with treatment refractory mental health conditions. At the same time, psychedelics remain in early stages of clinical investigation, have not yet achieved regulatory approval for general clinical use and may confer unique psychological and neurobiological effects that could raise novel ethical considerations when treating active-duty service members. Should psychedelics achieve regulatory approval, military relevant considerations may include issues of access to these treatments, appropriate procedures for informed consent, confidentiality standards, and possible unanticipated mental health risks and other psychological sequelae. A service member’s deployability, as well as their ability to return to full military duty following PAT, may also be of unique concern. The authors argue that MDMA-assisted therapy currently represents a promising treatment that should be more rapidly investigated as a clinical therapy for service members while still taking a measured approach that accounts for the many military-specific uncertainties that remain.